First Case Report of a Late Onset Knee Periprosthetic Joint Infection Caused by Lactococcus garvieae - V.-I. Neagoe; S. Zytoun; H.-J. Neuhaus (Case Reports in Orthopedics)
Lactococcus garvieae is known as a Gram-positive, catalase-negative, and facultatively anaerobic fish pathogen. The association between Lactococcus spp. and human infectious diseases is described as being mainly associated with lumbar osteomyelitis, hepatic abscess, and infective endocarditis. In the literature of orthopedic post-prosthetic infections, L. garvieae was associated with a case of hip prosthetic infection in a fishmonger woman. We present the case of a 79-year-old male patient with multiple comorbidities, who is admitted to our center with a 5-day history of pain, swelling, and motility disorder of the right knee by the presence of a bicondylar knee replacement surgery, which was performed due to gonarthrosis 17 years ago. The radiographies of the right knee revealed no signs of displacement or loosening of the prothesis. After multiple radical debridements including VAC therapy and targeted antibiotic therapy we have managed to defeat the infection without exchange arthroplasty. Although we could not demonstrate the source of infection, we can only presume that in our case the source of infection was represented by the ingestion of possibly contaminated food. The patient had a habit of eating Nile perch fish (Lates niloticus) every 4 weeks. We illustrated once more the possibility of a late onset L. garvieae related orthopedic periprosthetic joint infection by multiple comorbidities.